Keynes, Storytelling, and Realism:: Literary and Economic Discourse in Rohinton Mistry’s A Fine Balance - Tokaryk, Tyler (Studies in Canadian Literature / Études en littérature canadienne, 2005)
In opposition to logical positivism, John Maynard Keynes endorses "a language of vagueness" for economic development discourse that reflects a postmodern understanding of the limitations of language to reflect reality. Rohinton Mistry's A Fine Balance is a postmodern storytelling of India's economic development during the 1975-77 Emergency; its realist framework communicates the further elaboration required by Keynes's vague language to achieve a more precise rendering of the material world. The heteroglossia of voice and carnivalesque elements present in the narrative demonstrate a resistance, subversion, and ultimate delegitimization of the monologic, authoritative discourses of economic development. The homologous relationship between Mistry's postmodern storytelling and Keynes's "language of vagueness" reveals the common epistemological ground shared by literary and economic discourse, which should inspire more dialogue between the two disciplines.